2015
DOI: 10.1039/c5cc02316e
|View full text |Cite
|
Sign up to set email alerts
|

sp2–sp3diboranes: astounding structural variability and mild sources of nucleophilic boron for organic synthesis

Abstract: Despite the widespread use of organoborane reagents in organic synthesis and catalysis, a major challenge still remains: very few boron-centered nucleophiles exist for the direct construction of B-C bonds. Perhaps the most promising emerging solution to this problem is the use of sp(2)-sp(3) diboranes, in which one boron atom of a conventional diborane(4) is quaternised by either a neutral or anionic nucleophile. These compounds, either isolated or generated in situ, serve as relatively mild and convenient sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
165
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(188 citation statements)
references
References 172 publications
3
165
0
7
Order By: Relevance
“…Both of these factors limit the broader synthetic utility of such anionic boron species. A more operable approach to the realization of nucleophilic boron has been derived from the quaternisation of one of the three-coordinate boron centres of a diborane(4) molecule by a neutral or anionic nucleophile (for example, 5 and 6 )434445. Although the resultant adducts may act as viable surrogates for boron nucleophiles under (metal- and metal-free) catalytic conditions, these processes do not necessarily take place through the explicit generation of anionic boryl derivatives.…”
mentioning
confidence: 99%
“…Both of these factors limit the broader synthetic utility of such anionic boron species. A more operable approach to the realization of nucleophilic boron has been derived from the quaternisation of one of the three-coordinate boron centres of a diborane(4) molecule by a neutral or anionic nucleophile (for example, 5 and 6 )434445. Although the resultant adducts may act as viable surrogates for boron nucleophiles under (metal- and metal-free) catalytic conditions, these processes do not necessarily take place through the explicit generation of anionic boryl derivatives.…”
mentioning
confidence: 99%
“…[2] Many transition-metal complexes are known to be able to effectively cleave the B À Bb ond of diborane and catalyze the borylation or diboration of unsaturated organic substrates. [5] Recently,t he Lewis adducts of sp 2 -sp 3 diborane compounds have been reported for the borylation or diboration of unsaturated substrates. [5] Recently,t he Lewis adducts of sp 2 -sp 3 diborane compounds have been reported for the borylation or diboration of unsaturated substrates.…”
mentioning
confidence: 99%
“…[3,4] On the other hand, transitionmetal-free catalytic systems for activating the BÀB bond of diborane compounds have also attracted much attention. [5][6][7][8][9] It has been shown that diborane compounds became asource of nucleophilic boryl moiety,w hen one of the boron atoms of the diborane was tetracoordinated to as trong base (Scheme 1a). [5][6][7][8][9] It has been shown that diborane compounds became asource of nucleophilic boryl moiety,w hen one of the boron atoms of the diborane was tetracoordinated to as trong base (Scheme 1a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is reminiscent of previous alkoxide base mediated reactions developed by some of us 18, 19 and others. 20.21 A subsequent screening between various diphenyliodonium salts 1a-d and bis(pinacolato)diboron (2a) was undertaken and for the acetate derivative 1d confirmed the correctness of the initial hypothesis (Scheme 2). In agreement with previous experience, 18,19 methanol was identified as the best solvent.…”
Section: Scheme 1 Conceptual Approaches To Carbon-heteroatom Bond Fomentioning
confidence: 76%